2004
DOI: 10.1258/135763304322764149
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of following patients and assessing outcomes in teledermatology

Abstract: We retrospectively reviewed the follow-up and outcomes of 50 store-and-forward teledermatology patients, and compared the findings with those from a control group of 50 patients who had been seen in person. Patient records were examined for a six-month period following the initial referral to a dermatologist. Variables examined included medical records from the referral, evidence of actions taken (e.g. biopsy), evidence of follow-up visits, and what (if any) clinical outcomes were noted. There were few differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…In another study, dermatologists responded to store-and-forward consultations in an average of 2.17 days, compared with a mean wait time of 90 days for clinic-based appointments [12]. Two studies confirm that the clinical courses of TD patients and traditionally seen patients are similar [13,14]. Multiple studies have evaluated the proportion of store-and-forward TD consults that avoided, or would have avoided, a clinic visit to a dermatologist (ranging from 18-58%) and cutting in half the number of “urgent” referrals (from 64% to 32%) [15-21].…”
Section: Evaluations Of Tdmentioning
confidence: 99%
“…In another study, dermatologists responded to store-and-forward consultations in an average of 2.17 days, compared with a mean wait time of 90 days for clinic-based appointments [12]. Two studies confirm that the clinical courses of TD patients and traditionally seen patients are similar [13,14]. Multiple studies have evaluated the proportion of store-and-forward TD consults that avoided, or would have avoided, a clinic visit to a dermatologist (ranging from 18-58%) and cutting in half the number of “urgent” referrals (from 64% to 32%) [15-21].…”
Section: Evaluations Of Tdmentioning
confidence: 99%
“…5,14 Our data show that 68% of conditions required only one consultation, although the remaining one-third of conditions (32%) required two or more consultations. The tracking system facilitated treatment, particularly in cases with multiple consultations, by providing a detailed reference for previous treatment recommendation status and/or reasons why the treatment would not be completed (e.g.…”
Section: Discussionmentioning
confidence: 66%
“…To date, two studies have evaluated clinical outcomes of S&F teledermatology compared to conventional care, and both studies found similar outcomes for each of the two treatment modalities (Krupinski et al, 2004;Pak et al, 2007). Specifically, Pak et al conducted a randomized controlled trial with patients randomly assigned to either conventional face-toface care or teledermatology.…”
Section: Clinical Outcomes For Store-and-forward Teledermatologymentioning
confidence: 99%